2023
DOI: 10.1038/s41467-023-43889-6
|View full text |Cite
|
Sign up to set email alerts
|

GRAF1 integrates PINK1-Parkin signaling and actin dynamics to mediate cardiac mitochondrial homeostasis

Qiang Zhu,
Matthew E. Combs,
Juan Liu
et al.

Abstract: The serine/threonine kinase, PINK1, and the E3 ubiquitin ligase, Parkin, are known to facilitate LC3-dependent autophagosomal encasement and lysosomal clearance of dysfunctional mitochondria, and defects in this process contribute to a variety of cardiometabolic and neurological diseases. Although recent evidence indicates that dynamic actin remodeling plays an important role in PINK1/Parkin-mediated mitochondrial autophagy (mitophagy), the underlying signaling mechanisms remain unknown. Here, we identify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 76 publications
2
12
0
Order By: Relevance
“…We recently showed that GRAF1 promotes the release of damaged mitochondria from F-actin anchors, regulates mitochondrial-associated Arp2/3-mediated actin remodeling, and facilitates Parkin-LC3 interactions to enhance mitochondria capture by autophagosomes [ 39 ]. Our initial insight into GRAF1′s function largely centered on its ability to serve as a RhoA GAP to regulate actin remodeling-dependent mitophagy in Hela cells.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We recently showed that GRAF1 promotes the release of damaged mitochondria from F-actin anchors, regulates mitochondrial-associated Arp2/3-mediated actin remodeling, and facilitates Parkin-LC3 interactions to enhance mitochondria capture by autophagosomes [ 39 ]. Our initial insight into GRAF1′s function largely centered on its ability to serve as a RhoA GAP to regulate actin remodeling-dependent mitophagy in Hela cells.…”
Section: Resultsmentioning
confidence: 99%
“…As noted above, we observed a distinct GRAF1 band shift following OA treatment, suggesting a post-translational modification ( Figure 3 A, green arrow). Our previous study identified S668, T670, and S671 as the major GRAF1 phosphorylation sites mediated by the PINK1-Parkin pathway [ 39 ]. Notably, these amino acids exhibit partial conservation in other GRAF family members.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations